Eradication of Methicillin-Resistant Staphylococcus Aureus from the Lower Respiratory Tract of Patients with Cystic Fibrosis - David R Burdge; EM Nakielna; MA Noble (Canadian Journal of Infectious Diseases)
Two of 95 patients followed in an adult cystic fibrosis clinic consistently grew methicillin-resistant Staphylococcus aureus (mrsa) on sputum culture. Sputum Gram stain consistently showed +4 polymorphonuclear leukocytes and +4 Gram-positive cocci in clusters. Both patients were co-infected with Pseudomonas aeruginosa and required multiple hospitalizations for treatment of pulmonary exacerbation, resulting in significant infection control concerns. Multiple courses of antibiotics, including ciprofloxacin and clindamycin regimens, failed to eliminate the mrsa. A combination of oral rifampin and clindamycin was successful in eradicating the organism from both patients. Over a 12-month period following therapy, in both patients none of 13 sputums showed Gram-positive cocci in clusters on Gram stain and none of 13 sputum cultures grew mrsa. Successful eradication of mrsa has greatly simplified infection control measures on subsequent hospitalizations, reducing costs and enhancing patient comfort.